Sn plating material and method for producing the same

By forming Ni and Cu-Ni alloy base layers on the surface of copper or copper alloy base materials, and forming Cu-Sn-type alloy layer and Sn layer through heat treatment, the problems of high insertion force and high manufacturing cost of existing Sn plating materials are solved. , achieves low cost, low insertion force and good electrical performance Sn plating materials.

CN112593266BActive Publication Date: 2024-12-31DOWA METALTECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011428605.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2015-02-19
Filing Date
2015-02-25
Publication Date
2024-12-31
Estimated Expiration
2035-02-25

AI Technical Summary

Technical Problem

When used as pluggable connection terminals, the existing Sn plating materials have high insertion force and high manufacturing cost, making it difficult to achieve low-cost manufacturing.

Method used

The base layer of Ni and Cu-Ni alloy is formed on the surface of the copper or copper alloy substrate, and the Cu-Sn type alloy layer and the outermost Sn layer are formed by heat treatment to ensure that the area ratio of the Sn layer is between 20 and 80%, and the maximum The thickness is less than the average particle size of Cu-Sn type alloy, avoiding meshing and increasing insertion force.

Benefits of technology

The Sn-plating material for manufacturing pluggable connection terminals is achieved at a low cost, reducing insertion force and maintaining good electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112593266B_ABST
    Figure CN112593266B_ABST
Patent Text Reader

Abstract

In a Sn-plated material in which Sn plating is applied to the surface of a substrate (10) composed of copper or a copper alloy, a base layer (12) composed of at least one of Ni and Cu-Ni is formed on the surface of the substrate (10), and the surface of the base layer (12) is formed by a Cu-Sn alloy layer (14) composed of a large number of Cu-Sn alloy crystal grains, and an outermost layer composed of a Sn layer (16) located in a recess between adjacent Cu-Sn alloy crystal grains on the outermost surface, the area ratio of the Sn layer (16) on the outermost surface is 20 to 80%, and the maximum thickness of the Sn layer (16) is less than the average grain size of the Cu-Sn alloy crystal grains.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an Sn plating material and a method for manufacturing the same, and more particularly to an Sn plating material used as a material for a pluggable connection terminal or the like and a method for manufacturing the same. Background Art

[0002] Conventionally, as a material for a pluggable connection terminal, an Sn plating material in which Sn plating is applied to the outermost layer of a conductor material such as copper and copper alloy has been used. In particular, the Sn plating material has a small contact resistance and has been used as a material for the following products in consideration of contact reliability, corrosion resistance, solderability, economy, etc.: automobiles, information communication devices such as mobile phones and computers, control boards of industrial machines such as robots, and terminals and bus bars such as connectors, lead frames, relays, and switches.

[0003] As such an Sn plating material, the following plated copper or copper alloy has been proposed: a Ni or Ni alloy layer is formed on the surface of copper or copper alloy, an Sn or Sn alloy layer is formed on the outermost surface side, one or more intermediate layers mainly composed of Cu and Sn or intermediate layers mainly composed of Cu, Ni, and Sn are formed between the Ni or Ni alloy layer and the Sn or Sn alloy layer, and at least one of these intermediate layers contains a layer having a Cu content of 50% by weight or less and a Ni content of 20% by weight or less (for example, refer to Japanese Patent Laid-Open No. 2003-293187).

[0004] In addition, the following conductive material for a connection component has been proposed: a Cu-Sn alloy coating layer having a Cu content of 20 to 70 at% and an average thickness of 0.2 to 3.0 μm and an Sn coating layer having an average thickness of 0.2 to 5.0 μm are sequentially formed on the surface of a base material composed of a Cu strip, the surface is subjected to a reflow process, the arithmetic mean roughness Ra in at least one direction is 0.15 μm or more and the arithmetic mean roughness Ra in all directions is 3.0 μm or less, a part of the Cu-Sn alloy coating layer is exposed on the surface of the Sn coating layer, and the exposed area ratio of the surface of the Cu-Sn alloy coating layer is 3 to 75% (for example, refer to Japanese Patent Laid-Open No. 2006-183068).

[0005] However, although the Sn plating material of Japanese Patent Laid-Open No. 2003-293187 has good solderability, whisker resistance (Japanese: 耐ウィスカ性), heat resistance reliability, and formability, if this Sn plating material is used as a material for a pluggable connection terminal or the like, there is a problem that the insertion force becomes high when the connection terminal is inserted. In addition, in order to reduce the insertion force when the Sn plating material of Japanese Patent Laid-Open No. 2006-183068 is used as a material for a pluggable connection terminal or the like, it is necessary to roughen the surface of the base material and then apply plating, so the manufacturing cost becomes high. Summary of the invention

[0006] In view of the above-mentioned conventional problems, an object of the present invention is to provide a Sn-plated material having a low insertion force when used as a material for an electrical component such as a pluggable connecting terminal, and a method for producing the Sn-plated material at low cost.

[0007] The inventors of the present invention have conducted careful studies to solve the above-mentioned problems, and have found that in a Sn-plated material in which Sn plating is applied to the surface of a substrate composed of copper or a copper alloy, a base layer composed of at least one of Ni and a Cu-Ni alloy is formed on the surface of the substrate, and the surface of the base layer is formed by a Cu-Sn alloy layer composed of a large number of crystal grains of the Cu-Sn alloy, and an outermost layer composed of a Sn layer located in a recess between adjacent crystal grains of the Cu-Sn alloy on the outermost surface. By making the area ratio occupied by the Sn layer on the outermost surface 20 to 80% and the maximum thickness of the Sn layer smaller than the average grain size of the crystal grains of the Cu-Sn alloy, it is possible to manufacture a Sn-plated material with a low insertion force when used as a material for electrical components such as pluggable connecting terminals at a low cost, thereby completing the present invention.

[0008] That is, the Sn-plated material of the present invention is a Sn-plated material on the surface of a substrate composed of copper or a copper alloy, and the material is characterized in that a base layer composed of at least one of Ni and a Cu-Ni alloy is formed on the surface of the substrate, and the surface of the base layer is formed by a Cu-Sn alloy layer composed of a large number of Cu-Sn alloy grains, and an outermost layer composed of a Sn layer located in a recess between adjacent Cu-Sn alloy grains on the outermost surface, the area ratio of the Sn layer on the outermost surface is 20 to 80%, and the maximum thickness of the Sn layer is less than the average grain size of the Cu-Sn alloy grains.

[0009] In the Sn plating material, the Cu-Sn alloy layer is preferably composed of a Cu-Sn alloy and a Cu-Ni-Sn alloy. In this case, the Cu-Sn alloy is preferably composed of Cu 6 Sn 5 The Cu-Ni-Sn alloy is preferably composed of (Cu, Ni) 6 Sn 5 composition. In addition, the average particle size of the crystal grains of the Cu-Sn alloy is preferably 1.5 to 3 μm, the maximum thickness of the Sn layer is preferably 0.2 to 1.0 μm, and the average thickness of the Sn layer is preferably 0.05 to 0.4 μm. In addition, the thickness of the Cu-Sn alloy layer is preferably 0.4 to 1.5 μm, and the thickness of the base layer is preferably 0.05 to 0.5 μm. Furthermore, the arithmetic mean roughness Ra of the outermost surface is preferably 0.05 to 0.2 μm, and the maximum height Ry is preferably 0.3 to 1.5 μm.

[0010] In addition, the manufacturing method of the Sn-plated material of the present invention is characterized in that after treating the surface of a substrate composed of copper or a copper alloy, a Ni plating layer, a Cu plating layer and a Sn plating layer are formed on the surface of the substrate in sequence, and then a Cu-Sn alloy layer composed of a large number of Cu-Sn alloy grains and an outermost layer composed of a Sn layer located in a recess between adjacent Cu-Sn alloy grains on the outermost surface are formed by heat treatment, so that the area ratio occupied by the Sn layer in the outermost surface is 20 to 80%, and at the same time, the maximum thickness of the Sn layer is smaller than the average grain size of the Cu-Sn alloy grains.

[0011] In the manufacturing method of the Sn-plated material, it is preferred that the surface of the substrate is treated so that the arithmetic mean roughness Ra of the surface of the substrate is 0.05 to 0.2 μm, the maximum height Ry is 0.4 to 1.5 μm, and the ten-point average roughness Rz is 0.15 to 1.0 μm. In addition, it is preferred that the thickness of the Ni plating layer is 0.05 to 0.5 μm, the thickness of the Cu plating layer is 0.1 to 0.7 μm, and the thickness of the Sn plating layer is 0.5 to 1.5 μm. In addition, it is preferred that the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer is 1.5 to 5, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the thickness of the Ni plating layer is 1 to 3.5. Furthermore, it is preferred to set the temperature and time to perform the heat treatment so that the average grain size of the crystal grains of the Cu-Sn alloy in the temperature range of 300 to 800°C is 1.5 to 3 μm, and the maximum thickness of the Sn layer is 0.2 to 1.0 μm.

[0012] In addition, it is preferable to set the temperature and time to perform the heat treatment so that the average thickness of the Sn layer is 0.05 to 0.4 μm in the temperature range of 300 to 800° C. In this case, it is preferable to set the temperature and time of the heat treatment so that the thickness (μm) of the Sn plating layer further consumed after the Sn plating layer is melted by the heat treatment is greater than {the thickness of the Sn plating layer before the heat treatment (μm)-0.7 (μm)} and less than {the thickness of the Sn plating layer before the heat treatment (μm)-0.35 (μm)}.

[0013] Furthermore, the electric component of the present invention is characterized in that the above-mentioned Sn-plated material is used as a material.

[0014] According to the present invention, it is possible to manufacture at low cost a Sn-plated material having a low insertion force when used as a material for an electrical component such as a pluggable connection terminal.

[0015] BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view schematically showing an embodiment of the Sn-plated material of the present invention.

[0017] Figure 2 This is a graph showing the angle θ between the outermost surface of the Cu-Sn alloy layer and the intersection of a straight line passing through a point of maximum depth of the Sn layer and the approximate center position of the outermost surface of the Cu-Sn alloy layer adjacent to the Sn layer in a cross section approximately perpendicular to the outermost surface of an embodiment of the Sn-plated material of the present invention. DETAILED DESCRIPTION

[0018] The Sn plating material of the present invention is as follows Figure 1 As shown, in a Sn-plated material in which Sn plating is applied to the surface of a substrate 10 composed of copper or a copper alloy, a base layer 12 composed of at least one of Ni and a Cu-Ni alloy is formed on the surface of the substrate 10, and the surface of the base layer 12 forms an outermost layer composed of a Cu-Sn alloy layer 14 composed of a large number of crystal grains of the Cu-Sn alloy and a Sn layer 16 located in a concave portion between adjacent crystal grains of the Cu-Sn alloy on the outermost surface, and the area ratio occupied by the Sn layer 16 on the outermost surface is 20 to 80% (preferably 30 to 75%, more preferably 30 to 70%), and the maximum thickness of the Sn layer 16 is smaller than the average grain size of the crystal grains of the Cu-Sn alloy. If the Sn-plated material thus constructed is used as a material for a pluggable connection terminal, the meshing of the outermost Cu-Sn alloy layer can be prevented, and a connection terminal with low insertion force and low resistance value during slight sliding can be manufactured.

[0019] In the Sn plating material, the Cu-Sn alloy layer 14 is preferably composed of a Cu-Sn alloy and a Cu-Ni-Sn alloy. In this case, the Cu-Sn alloy is preferably composed of Cu 6 Sn 5 The Cu-Ni-Sn alloy is preferably composed of (Cu, Ni) 6 Sn 5 (Cu 6 Sn 5In addition, the average particle size of the crystal grains of the Cu-Sn alloy is preferably 1.5 to 3 μm. In addition, the maximum thickness of the Sn layer 16 is preferably 0.2 to 1.0 μm, and more preferably 0.3 to 0.9 μm. In addition, the ratio (D / T) of the average particle size (D) of the crystal grains of the outermost Cu-Sn alloy to the maximum thickness (T) of the Sn layer 16 is preferably 1.5 to 10, more preferably 2 to 7, and most preferably 2 to 6. In addition, the average thickness of the Sn layer 16 is preferably 0.05 to 0.4 μm, and more preferably 0.05 to 0.3 μm. In addition, the thickness of the Cu-Sn alloy layer 14 is preferably 0.4 to 1.5 μm, and more preferably 0.5 to 1.2 μm. In addition, the thickness of the base layer 12 is preferably 0.05 to 0.5 μm, and more preferably 0.1 to 0.4 μm. Furthermore, it is preferred that the arithmetic mean roughness Ra of the outermost surface is 0.05 to 0.2 μm and the maximum height Ry is 0.3 to 1.5 μm.

[0020] Accordingly, in an embodiment of the Sn-plated material of the present invention, a base layer 12 composed of at least one of Ni and a Cu-Ni alloy is preferably formed on the surface of the substrate 10, an outermost layer composed of a Cu-Sn alloy layer 14 and a Sn layer 16 is formed on the surface of the base layer 12, and there is no layer composed of Cu as an intermediate layer between the base layer 12 and the outermost layer.

[0021] In addition, in the cross section of the Sn-plated material substantially perpendicular to the outermost surface, the angle θ between the straight line passing through the point of intersection of the maximum depth of the Sn layer and the approximate center position of the outermost surface of the Cu-Sn alloy layer adjacent to the Sn layer and the outermost surface of the Cu-Sn alloy layer is preferably 25 to 45°. That is, Figure 2As shown, in a cross section of the Sn-plated material that is approximately perpendicular to the outermost surface, a straight line L1 parallel to the outermost surface is drawn from a point A1 where one crystal grain of the Cu-Sn alloy of the Cu-Sn alloy layer 14 contacts one of the crystal grains of the Cu-Sn alloy on both sides and serves as the maximum depth of the Sn layer 16 between these crystal grains, a straight line L2 parallel to the outermost surface is drawn from a point A2 where one crystal grain of the Cu-Sn alloy contacts the other of the crystal grains of the Cu-Sn alloy on both sides and serves as the maximum depth of the Sn layer 16 between these crystal grains, and a straight line L1 parallel to the outermost surface is drawn between the straight lines L1 and L2. A straight line L3 that is equidistant on both sides of the straight line L2 and parallel to the outermost surface (a straight line L3 that represents the average depth of points A1 and A2, which are the maximum depths of the Sn layer 16 on both sides of the crystal grains of the Cu-Sn alloy in a section approximately perpendicular to the outermost surface of the Sn-plated material), a perpendicular line drawn from the midpoint of the line segment between the intersection B1 of the perpendicular line passing through point A1 to the outermost surface and the straight line L3 and the intersection B2 of the perpendicular line passing through point A2 to the outermost surface and the straight line L3 is B3, and the angle θ between the straight line connecting the intersection B3 and the intersection B1 and the outermost surface is preferably 25 to 45°. The angle θ can be calculated, for example, by cutting the Sn-plated material with a focused ion beam (FIB) to expose a section approximately perpendicular to the outermost surface of the Sn-plated material and parallel to the rolling direction (or a section approximately perpendicular to the outermost surface of the Sn-plated material and approximately perpendicular to the rolling direction), observing the section with a scanning electron microscope (SEM) (for example, at 10,000 times), and determining the angle θ. Figure 2 Let L be the length of the line segment between the intersection B1 and the intersection B2 shown, and let H be the length between the midpoint of the intersection B1 and the intersection B2 and the intersection point of the perpendicular line from the midpoint of the intersection B1 and the intersection B2 to the outermost surface and the outermost surface. Then tanθ is approximately equal to H / (L / 2), and the angle θ can be calculated by tanθ=H / (L / 2).

[0022] In an embodiment of the manufacturing method of the Sn-plated material of the present invention, after the surface of a substrate composed of copper or a copper alloy is treated, a Ni plating layer, a Cu plating layer and a Sn plating layer are formed on the surface of the substrate in sequence, and then a Cu-Sn alloy layer composed of a large number of Cu-Sn alloy grains and an outermost layer composed of a Sn layer located in a recess between adjacent Cu-Sn alloy grains on the outermost surface are formed by heat treatment, so that the area ratio occupied by the Sn layer in the outermost surface is 20 to 80% (preferably 30 to 75%, and more preferably 30 to 70%), and at the same time, the maximum thickness of the Sn layer is less than the average grain size of the Cu-Sn alloy grains.

[0023] In the method for manufacturing the Sn-plated material, it is preferred that the surface of the substrate is treated so that the arithmetic mean roughness Ra of the substrate surface is 0.05 to 0.2 μm, the maximum height Ry is 0.4 to 1.5 μm, and the ten-point average roughness Rz is 0.15 to 1.0 μm. As a method for treating the surface of the substrate to reduce the surface roughness of the substrate (to a desired value) and reduce the surface unevenness, a chemical polishing method such as electrolytic polishing and a mechanical polishing method such as rolling, grinding and sandblasting of the substrate using a work roll whose surface roughness has been reduced by polishing can be used.

[0024] In addition, the thickness of the Ni plating layer is preferably 0.05 to 0.5 μm, and more preferably 0.05 to 0.4 μm. The thickness of the Cu plating layer is preferably 0.1 to 0.7 μm, and more preferably 0.1 to 0.5 μm. The thickness of the Sn plating layer is preferably 0.5 to 1.5 μm, and more preferably 0.6 to 1.2 μm. In addition, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer (Sn thickness / Cu thickness) is preferably 1.5 to 5, and more preferably 2 to 5. In addition, the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer (Sn thickness / (Cu thickness+Ni thickness)) is preferably 1 to 3.5.

[0025] In addition, it is preferred to perform heat treatment in an atmosphere at a temperature of 300 to 800° C. for 1 to 1800 seconds (until the outermost layer consisting of a Cu-Sn alloy layer consisting of a large number of Cu-Sn alloy crystal grains and a Sn layer located in a concave portion between adjacent Cu-Sn alloy crystal grains on the outermost surface is formed, so that the area ratio occupied by the Sn layer in the outermost surface is 20 to 80%, and the maximum thickness of the Sn layer is less than the average grain size of the Cu-Sn alloy crystal grains) in the atmospheric atmosphere. It is preferred to set the temperature and time to perform the heat treatment so that the average grain size of the Cu-Sn alloy crystal grains in the temperature range of 300 to 800° C. is 1.5 to 3 μm, and the maximum thickness of the Sn layer is 0.2 to 1.0 μm.

[0026] In addition, it is preferable to set the temperature and time to perform the heat treatment so that the average thickness of the Sn layer is 0.05 to 0.4 μm in the temperature range of 300 to 800°C (in order to reduce the amount of agglomeration at the contact point when the Sn-plated material is used as a material for a pluggable connection terminal, etc.). In order to perform the heat treatment in the temperature range of 300 to 800°C so that the average thickness of the Sn layer is 0.05 to 0.4 μm, the heat treatment is continued until the average thickness of the Sn layer remaining after the Sn melts is 0.05 to 0.4 μm. That is, after the Ni plating layer, the Cu plating layer, and the Sn plating layer are formed on the surface of the substrate in sequence, if the heat treatment is performed in the temperature range of 300 to 800°C, the thickness of the Sn plating layer consumed until the temperature (232°C) at which the melting point of Sn is reached (the value obtained by evaluating the test in advance) is 0.3 μm, and the thickness of the Sn plating layer consumed due to the diffusion of the liquid Sn after the Sn melts is {2×diffusion coefficient D(m 2 / s)×holding time t(s)} 1 / 2 Therefore, in order to make the average thickness of the Sn layer 0.05 to 0.4 μm by heat treatment, the temperature and time of the heat treatment are set so that {the thickness of the Sn plating layer before the heat treatment T Sn (μm)-the thickness of the Sn plating layer consumed until Sn melts 0.3 (μm)-the average thickness of the Sn plating layer remaining after Sn melts 0.4 (μm)}≦{2×diffusion coefficient D×holding time t} 1 / 2 (μm) ≦ {Thickness of Sn plating layer before heat treatment T Sn (μm)-the thickness of the Sn plating layer consumed before Sn melting 0.3 (μm)-the average thickness of the Sn plating layer remaining after Sn melting 0.05 (μm)}. That is, in order to make the average thickness of the Sn layer 0.05 to 0.4 μm, the temperature and time of the heat treatment are set so that the thickness (μm) of the Sn plating layer further consumed after the Sn plating layer is melted by the heat treatment is within {the thickness of the Sn plating layer before the heat treatment T Sn (μm)-0.7 (μm)} or more and in {the thickness of the Sn plating layer before heat treatment T Sn (μm)-0.35(μm)} or less. In addition, the diffusion coefficient D(m 2 / s) based on the vibration frequency factor D 0 (=1.7×10 -15 (m 2 / s)), activation energy Q (=-19.4 (J / mol)), gas constant R (=8.314 J / mol·K) and temperature T (K) are expressed as D=D 0exp(-Q / RT), so the thickness (μm) of the Sn plating layer that is further consumed after the Sn plating layer is melted by the heat treatment is a function of temperature and time, and the temperature and time of the heat treatment can be set.

[0027] Next, embodiments of the Sn-plated material and the method for producing the same according to the present invention will be described in detail.

[0028] Example 1

[0029] First, a flat plate-shaped conductor substrate (a copper alloy substrate containing 1.0 mass % Ni, 0.9 mass % Sn, 0.05 mass % P, and the balance Cu) composed of a Cu-Ni-Sn-P alloy with a thickness of 0.25 mm was prepared, and the surface of the substrate was treated with a ceramic rolling roll (a rolling roll whose surface was polished by a grinding stone (#400) using a rolling roll polisher to reduce the maximum height Ry and the ten-point average roughness Rz of the surface) to reduce the surface roughness. Regarding the surface roughness of the substrate after such surface treatment, the arithmetic mean roughness Ra, the maximum height Ry, and the ten-point average roughness Rz, which are parameters representing the surface roughness, were calculated according to JIS B0601 (1994) using the measurement results of the rolling surface in the direction perpendicular to the rolling direction measured by a contact surface roughness measuring instrument (Surfcorder SE4000 manufactured by Kosaka Laboratory Co., Ltd.). As a result, the arithmetic mean roughness Ra was 0.15 μm, the maximum height Ry was 1.05 μm, and the ten-point average roughness Rz was 0.71 μm. In addition, the average interval Sm of the concavities and convexities on the substrate surface was measured using a contact surface roughness measuring instrument (Surfcorder SE4000 manufactured by Kosaka Laboratory Co., Ltd.), and the result was 80 μm.

[0030] Next, as a pretreatment, the surface treated substrate (plating substrate) was electrolytically degreased for 10 seconds using an alkaline electrolytic degreasing solution and washed with water, and then acid-washed by immersing in 5 mass % sulfuric acid for 10 seconds and then washed with water.

[0031] Then, in a Ni plating solution containing 80 g / L of nickel sulfamate and 45 g / L of boric acid, the surface treated substrate (plated substrate) was used as a cathode and the Ni electrode plate was used as an anode at 5 A / dm 2 Electroplating was performed at a current density of 1000 Å and a liquid temperature of 50° C. for 5 seconds, thereby forming a Ni plating layer with a thickness of 0.1 μm on the substrate.

[0032] Then, in a Cu plating solution containing 110 g / L of copper sulfate and 100 g / L of sulfuric acid, the Ni-plated substrate was used as a cathode and the Cu electrode plate was used as an anode at 5 A / dm2 Electroplating was performed at a current density of 1.000 Å and a liquid temperature of 30° C. for 16 seconds, thereby forming a Cu plating layer with a thickness of 0.4 μm on the substrate.

[0033] Then, in a Sn plating solution containing 60 g / L of stannous sulfate, 75 g / L of sulfuric acid, 30 g / L of cresol sulfonic acid, and 1 g / L of β-naphthol, the Cu-plated substrate was used as the cathode and the Sn electrode plate was used as the anode. 2 Electroplating was performed at a current density of 1.0 μm and a liquid temperature of 25° C. for 20 seconds, thereby forming a Sn plating layer with a thickness of 1.0 μm on the substrate.

[0034] In the Sn-plated plated substrate, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.5, and the ratio of the thickness of the Sn plating layer to the sum of the thicknesses of the Cu plating layer and the Ni plating layer was 2.

[0035] Next, the plated material subjected to Sn plating was washed and dried, and then placed in a bright annealing furnace (manufactured by Koyo Lindberg Co., Ltd.), and heat-treated at a furnace temperature of 400° C. for 150 seconds in an air atmosphere. In this embodiment, of the 150 seconds of heat treatment holding time, the holding time after Sn melting was 90 seconds, and the average thickness of Sn consumed after Sn melting was calculated to be 0.37 μm.

[0036] The outermost layer formed on the outermost surface of the Sn-plated material thus prepared was analyzed by electron probe microanalysis (EPMA) and Auger electron spectroscopy (AES), and it was confirmed that the outermost layer was composed of Sn and Cu. 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, when the thickness of these layers is measured by an electrolytic film thickness meter (Thickness Tester TH-11 manufactured by Chuo Seisakusho Co., Ltd.), the average thickness of the Sn layer is 0.23 μm, and the thickness of the Cu-Sn alloy layer is 0.90 μm. In addition, after the Sn layer on the surface of the Sn-plated material is stripped using a Sn stripping solution (containing p-nitrophenol and caustic soda), the crystal grain size of the Cu-Sn alloy on the exposed surface is obtained according to the cutting method of JIS H0501, and the average grain size of the crystal grains of the Cu-Sn alloy on the outermost surface is calculated to be 2.8 μm.

[0037] In addition, after AES analysis, the base layer formed on the surface of the substrate of the Sn-plated material was found to be composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer was 0.10 μm. In addition, when AES was used to analyze whether there was an intermediate layer between the outermost layer and the base layer of the Sn-plated material, it was found that there was no Cu layer as an intermediate layer, and the outermost layer was formed on the surface of the base layer.

[0038] In addition, Au with a thickness of about 200 nm was vapor-deposited on the outermost surface of the Sn-plated material, and the material was cut using a focused ion beam (FIB) to expose a cross-section perpendicular to the rolling direction of the Sn-plated material. A scanning electron microscope (SEM) was used to observe 10 positions in a field of view with a length of L (=20 μm) parallel to the surface of the Sn-plated material in the cross-section at a magnification of 5000 times. In each observation area, the total length (Lm) of the contact between the Cu-Sn alloy layer and the Au vapor-deposited layer was subtracted from the length L (=20 μm) of the entire area, and the result was divided by the length L of the entire area (the ratio of the contact length between the Sn layer and the Au vapor-deposited layer in the observation area = (L-Lm) / L). The maximum and minimum values ​​of the values ​​obtained in the 10 observation areas were removed, and the average value of the values ​​in the remaining 8 observation areas was multiplied by 100 to obtain the area ratio of Sn (the area occupied by the Sn layer in the outermost surface). The calculated result of the area ratio of Sn was 57%.

[0039] In addition, the Sn-plated material was cut with a focused ion beam (FIB) to expose a section perpendicular to the rolling direction of the Sn-plated material, and a scanning electron microscope (SEM) was used to observe three positions in the section with a length of about 30 μm parallel to the surface of the Sn-plated material at a magnification of 5000 times, and the maximum depth of the concave portion (the maximum thickness of the Sn layer (the depth of existence of pure Sn)) was 0.75 μm. In addition, the calculated result of the ratio (D / T) of the average grain size (D) of the Cu-Sn alloy to the maximum thickness (T) of the Sn layer was 3.73.

[0040] In addition, regarding the surface roughness of the Sn-plated material, the arithmetic mean roughness Ra and the maximum height Ry were calculated by the same method as above. The arithmetic mean roughness Ra and the maximum height Ry of the surface of the Sn-plated material were 0.16 μm and 1.13 μm respectively.

[0041] In addition, the Sn-plated material was cut with a focused ion beam (FIB) to expose two sections approximately perpendicular to the outermost surface of the Sn-plated material and parallel to the rolling direction, and two sections approximately perpendicular to the outermost surface of the Sn-plated material and perpendicular to the rolling direction, as sections approximately perpendicular to the outermost surface of the Sn-plated material. Each section was observed with a scanning electron microscope (SEM) at a magnification of 10,000 times. By observing these sections, it was confirmed that a Cu-Sn alloy layer composed of crystal grains of a Cu-Sn alloy and a Sn layer composed of Sn formed between the crystal grains existed on the outermost surface of the Sn-plated material. In each section, as shown in FIG. Figure 2 As shown, a straight line L1 parallel to the outermost surface is drawn from a point A1 where a crystal grain of the Cu-Sn alloy of the Cu-Sn alloy layer 14 contacts one side of the crystal grains of the Cu-Sn alloy on both sides and serves as the maximum depth of the Sn layer 16 between these crystal grains, and a straight line L2 parallel to the outermost surface is drawn from a point A2 where a crystal grain of the Cu-Sn alloy contacts the other side of the crystal grains of the Cu-Sn alloy on both sides and serves as the maximum depth of the Sn layer 16 between these crystal grains, and A straight line L3 is drawn between the straight lines L1 and L2, which is equidistant from both the straight lines L1 and L2 and parallel to the outermost surface. The intersection point B1 between the perpendicular line drawn from the point A1 to the outermost surface and the straight line L3 and the intersection point B2 between the perpendicular line drawn from the point A2 to the outermost surface and the straight line L3 is B3, and the angle θ between the straight line connecting the intersection point B3 and the intersection point B1 and the outermost surface is calculated. As a result, the average value of the angle θ in each section is 27.7°. In addition, the length of the line segment between the intersection point B1 and the intersection point B2 is L, and the length between the midpoint of the intersection point B1 and the intersection point B2 and the perpendicular line drawn from the midpoint of the intersection point B1 and the intersection point B2 to the outermost surface and the intersection point B3 of the outermost surface is H, then tanθ is approximately equal to H / (L / 2), and the angle θ can be calculated by tanθ=H / (L / 2).

[0042] In addition, in order to evaluate the insertion force when the Sn-plated material is used as a pluggable connection terminal or other material, the Sn-plated material is fixed on a horizontal load measuring instrument (a device composed of an electric contact simulator, a test bench controller, a force sensor, and a force sensor amplifier manufactured by Yamazaki Seiki Laboratories, Ltd.), and the indenter is brought into contact with the evaluation sample. The indenter is pressed against the surface of the Sn-plated material with a load of 0.7N and 5N, respectively, and the Sn-plated material is pulled horizontally at a sliding speed of 80mm / min for a sliding distance of 10mm. The force applied in the horizontal direction between 1mm and 4mm (sliding distance 3mm) is measured, and the average value F is calculated. The dynamic friction coefficient (μ) between the test pieces is calculated by μ=F / N. As a result, the dynamic friction coefficients at loads of 0.7N and 5N are 0.25 and 0.23, respectively.

[0043] In addition, the contact resistance value of the test piece cut out from the Sn-plated material was measured to be 1.1 mΩ. In addition, in order to evaluate the contact reliability of the Sn-plated material after being placed at high temperature, the test piece cut out from the Sn-plated material was kept in a constant temperature bath at 120°C for 120 hours under an atmospheric atmosphere, and then taken out from the constant temperature bath, and the contact resistance value (contact resistance value after high temperature placement) of the surface of the test piece in the measuring room at 20°C was measured, and the contact resistance value after high temperature placement was 25 mΩ. In addition, using a micro-ohmmeter, the contact resistance value was measured 5 times under the conditions of open circuit voltage 20mV, current 10mA, U-shaped gold wire probe with a diameter of 0.5mm, maximum load 100gf, and sliding (1mm / 100gf), and the average value (when the maximum load of 100gf was applied) was obtained.

[0044] In addition, two test pieces were cut out from the Sn-plated material, one of the test pieces was used as a flat test piece (a test piece as a male terminal), and the other test piece was subjected to indentation processing (hemispherical indentation processing with an R of 1 mm) to use as a test piece with indentation (a test piece as a female terminal), and the flat test piece was fixed to a test table of an electric micro-sliding wear tester, and after the flat test piece was brought into contact with the indentation of the test piece with indentation, the test piece with indentation was pressed against the surface of the flat test piece with grooves with a load of 0.7 N, and the test table to which the flat test piece was fixed was slid 70 times within a one-way range of 50 μm at a sliding speed of one back and forth per second to implement a sliding test, and the resistance value of the contact point between the flat test piece with grooves and the test piece with indentation after the sliding test was continuously measured by a four-terminal method. As a result, the maximum value of the resistance value in the sliding test was a low value of 8.5 mΩ.

[0045] Example 2

[0046] Except that the thickness of the Cu plating layer was 0.2 μm, a Sn-plated material was produced by the same method as in Example 1. In this example, the holding time after Sn melting was 90 seconds out of the 150 seconds of the heat treatment holding time, and the calculated result of the thickness of Sn consumed after Sn melting was 0.37 μm.

[0047] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated. The contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 5, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 3.3.

[0048] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.22 μm, and the thickness of the Cu-Sn alloy layer is 0.55 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with residual Sn), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.7 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the Cu-Sn alloy in the outermost layer to the maximum thickness (T) of the Sn layer is 3.09. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 56%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.55 μm.

[0049] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.10 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0050] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.14 μm, the maximum height Ry is 0.85 μm, and the average value of the angle θ is 38.8°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.29 and 0.24, respectively. In addition, the contact resistance value is 1.5 mΩ, and the contact resistance value after high temperature placement is 21 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 18 mΩ.

[0051] Example 3

[0052] The Sn-plated material was prepared by the same method as in Example 1 except that the arithmetic mean roughness Ra of the substrate after the surface treatment was 0.08 μm, the maximum height Ry was 0.69 μm, the ten-point average roughness Rz was 0.53 μm, the thickness of the Ni plating layer was 0.3 μm, the thickness of the Cu plating layer was 0.3 μm, the thickness of the Sn plating layer was 0.7 μm, and the holding time of the heat treatment was 105 seconds. In this example, the holding time after the Sn melted was 45 seconds out of the 105 seconds of the holding time of the heat treatment, and the calculated result of the thickness of the Sn consumed after the Sn melted was 0.26 μm.

[0053] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated. The contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.3, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.16.

[0054] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5(Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.08 μm, and the thickness of the Cu-Sn alloy layer is 0.70 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with Sn remaining), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.6 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the Cu-Sn alloy in the outermost layer to the maximum thickness (T) of the Sn layer is 5.33. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 35%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.30 μm.

[0055] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.30 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0056] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.14 μm, the maximum height Ry is 1.01 μm, and the average value of the angle θ is 35.5°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.24 and 0.23, respectively. In addition, the contact resistance value is 1.3 mΩ, and the contact resistance value after high temperature placement is 48 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 9.5 mΩ.

[0057] Example 4

[0058] The Sn-plated material was prepared by the same method as in Example 1 except that the thickness of the Cu plating layer was 0.3 μm, the thickness of the Sn plating layer was 0.7 μm, the heat treatment temperature was 600°C, and the holding time was 40 seconds. In this example, the holding time after the Sn melted was 30 seconds in the 40 seconds of the heat treatment holding time, and the calculated result of the thickness of the Sn consumed after the Sn melted was 0.32 μm.

[0059] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated, and the contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.3, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.75.

[0060] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.07 μm, and the thickness of the Cu-Sn alloy layer is 0.70 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with Sn remaining), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.5 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the Cu-Sn alloy in the outermost layer to the maximum thickness (T) of the Sn layer is 4.29. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 51%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.35 μm.

[0061] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.10 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0062] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.16 μm, the maximum height Ry is 1.19 μm, and the average value of the angle θ is 32.2°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.22 and 0.25, respectively. In addition, the contact resistance value is 1.2 mΩ, and the contact resistance value after high temperature placement is 10 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 8.0 mΩ.

[0063] Example 5

[0064] The Sn-plated material was prepared by the same method as in Example 1 except that the arithmetic mean roughness Ra of the substrate after surface treatment was 0.12 μm, the maximum height Ry was 0.95 μm, the ten-point average roughness Rz was 0.68 μm, the heat treatment temperature was 700°C, and the holding time was 13 seconds. In this example, the holding time after Sn melting was 6.5 seconds out of the 13 seconds of the heat treatment holding time, and the calculated result of the thickness of Sn consumed after Sn melting was 0.31 μm.

[0065] For the Sn-plated material thus prepared, the plating layer analysis was performed in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated, and the contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.5, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 2.

[0066] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.29 μm, and the thickness of the Cu-Sn alloy layer is 0.95 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with Sn remaining), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.9 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the outermost Cu-Sn alloy to the maximum thickness (T) of the Sn layer was 2.11. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 67%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.90 μm.

[0067] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.10 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0068] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.17 μm, the maximum height Ry is 1.18 μm, and the average value of the angle θ is 28.5°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.25 and 0.24, respectively. In addition, the contact resistance value is 1.3 mΩ, and the contact resistance value after high temperature placement is 22 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 7.5 mΩ.

[0069] Example 6

[0070] The Sn-plated material was prepared by the same method as in Example 1 except that the arithmetic mean roughness Ra of the substrate after the surface treatment was 0.08 μm, the maximum height Ry was 0.69 μm, the ten-point average roughness Rz was 0.53 μm, the thickness of the Ni plating layer was 0.3 μm, the thickness of the Cu plating layer was 0.3 μm, the thickness of the Sn plating layer was 0.7 μm, and the holding time of the heat treatment was 120 seconds. In this example, the holding time after the Sn melted was 60 seconds in the 120 seconds of the holding time of the heat treatment, and the calculated result of the thickness of the Sn consumed after the Sn melted was 0.31 μm.

[0071] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated. The contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.3, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.16.

[0072] As a result, it was confirmed that the outermost layer was composed of Sn and (Cu, Ni) 6 Sn 5(Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.07 μm, and the thickness of the Cu-Sn alloy layer is 0.70 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with Sn remaining), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.7 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the outermost Cu-Sn alloy to the maximum thickness (T) of the Sn layer is 5.67. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 45%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.30 μm.

[0073] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.30 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0074] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.15 μm, the maximum height Ry is 1.15 μm, and the average value of the angle θ is 35.5°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.25 and 0.25, respectively. In addition, the contact resistance value is 1.2 mΩ, and the contact resistance value after high temperature placement is 50 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 9.0 mΩ.

[0075] Example 7

[0076] The Sn-plated material was prepared by the same method as in Example 1, except that the arithmetic mean roughness Ra of the surface treated substrate was 0.07 μm, the maximum height Ry was 0.52 μm, the ten-point average roughness Rz was 0.41 μm, the thickness of the Ni plating layer was 0.1 μm, the thickness of the Cu plating layer was 0.3 μm, the thickness of the Sn plating layer was 0.6 μm, the heat treatment temperature was 700°C, and the heat treatment holding time was 5 seconds.

[0077] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated, and the contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.5.

[0078] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.14μm, and the thickness of the Cu-Sn alloy layer is 0.70μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with residual Sn), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 2.5μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the Cu-Sn alloy in the outermost layer to the maximum thickness (T) of the Sn layer was 6.76. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 63%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.37 μm.

[0079] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.1 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0080] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.06 μm, and the maximum height Ry is 0.45 μm. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.21 and 0.22, respectively. In addition, the contact resistance value is 1.5 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 16.1 mΩ.

[0081] Comparative Example 1

[0082] A Sn-plated material was prepared by the same method as in Example 1, except that the surface of the substrate was processed with a ceramic rolling roll whose surface was not polished, the arithmetic mean roughness Ra was 0.15 μm, the maximum height Ry was 1.78 μm, the ten-point average roughness Rz was 1.15 μm, the thickness of the Ni plating layer was 0.3 μm, the thickness of the Cu plating layer was 0.7 μm, the thickness of the Sn plating layer was 0.7 μm, the heat treatment temperature was 600° C., and the holding time was 20 seconds. In this comparative example, the holding time after Sn melting was 10 seconds out of the 20 seconds of the heat treatment holding time, and the calculated result of the thickness of Sn consumed after Sn melting was 0.19 μm.

[0083] For the Sn-plated material thus prepared, the plating layer was analyzed by the same method as in Example 1, and the surface average roughness Ra and maximum height Ry, the dynamic friction coefficient, the contact resistance value, and the maximum resistance value in the sliding test were calculated. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 1, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 0.7.

[0084] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.04μm, and the thickness of the Cu-Sn alloy layer is 0.95μm. In addition, the shape of the particles of the Cu-Sn alloy layer was not confirmed by SEM, and it was confirmed that a concave portion was formed (Sn remained) on the surface of the mutually bonded Cu-Sn alloy layer. In addition, the area occupied by the Sn layer in the outermost surface (the area ratio of Sn) is 8%, and the maximum depth of the concave portion (the maximum thickness of the Sn layer) is 0.15μm.

[0085] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and its thickness is 0.30 μm. In addition, a Cu layer with a thickness of 0.20 μm is not formed as an intermediate layer between the outermost layer and the base layer of the Sn-plated material, and the outermost layer is formed on the surface of the intermediate layer.

[0086] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.23 μm, and the maximum height Ry is 1.85 μm. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.38 and 0.29, respectively. In addition, the contact resistance value is 1.4 mΩ, and the contact resistance value after high temperature placement is 24 mΩ. In addition, the maximum value of the resistance value in the sliding test is a high value of 150 mΩ.

[0087] Comparative Example 2

[0088] A Sn-plated material was prepared by the same method as in Example 1, except that the surface of the substrate was processed with a ceramic rolling roll whose surface was not polished, the arithmetic mean roughness Ra was 0.15 μm, the maximum height Ry was 1.65 μm, the ten-point average roughness Rz was 0.94 μm, Ni plating and Cu plating were not performed, the heat treatment temperature was 700° C., and the holding time was 6.5 seconds. In this comparative example, the holding time after Sn melting was 0 seconds in the heat treatment holding time of 6.5 seconds, and the calculated result of the thickness of Sn consumed after Sn melting was 0 μm.

[0089] For the Sn-plated material produced in this way, the plating layer was analyzed by the same method as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated. At the same time as the contact resistance value, the maximum resistance value in the sliding test was obtained.

[0090] As a result, the outermost layer of the Sn-plated material was composed of Sn, and the thickness of the Sn layer was 0.57 μm. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 100%, and the maximum depth of the recess (maximum thickness of the Sn layer) was 1.00 μm.

[0091] In addition, as a base layer formed on the surface of the substrate of the Sn-plated material, a Cu layer having a thickness of 0.90 μm was formed. 6 Sn 5 The Cu-Sn alloy layer formed was observed by SEM after the outermost Sn layer was removed, and the average particle size of the crystal grains of the Cu-Sn alloy was calculated, and the result was 1.1 μm. In addition, the calculation result of the ratio (D / T) of the average particle size (D) of the crystal grains of the outermost Cu-Sn alloy to the maximum thickness (T) of the Sn layer was 1.10. In addition, there is no Cu layer as an intermediate layer between the outermost layer and the substrate of the Sn-plated material, and the outermost layer is formed on the surface of the base layer.

[0092] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.06 μm, the maximum height Ry is 0.49 μm, and the average value of the angle θ is 56.0°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.41 and 0.32, respectively. In addition, the contact resistance value is 1.2 mΩ, and the contact resistance value after high temperature placement is 110 mΩ. In addition, the maximum value of the resistance value in the sliding test is a low value of 25 mΩ.

[0093] Comparative Example 3

[0094] The Sn-plated material was prepared by the same method as in Example 1 except that the thickness of the Cu plating layer was 0.2 μm, the thickness of the Sn plating layer was 0.5 μm, the heat treatment temperature was 600°C, and the holding time was 30 seconds. In this comparative example, the holding time after the Sn melted was 20 seconds out of the 30 seconds of the heat treatment holding time, and the calculated result of the thickness of the Sn consumed after the Sn melted was 0.26 μm.

[0095] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the dynamic friction coefficient, the contact resistance value, and the maximum resistance value in the sliding test were calculated. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.5, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.7.

[0096] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5 (Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.04μm, and the thickness of the Cu-Sn alloy layer is 0.45μm. In addition, the shape of the particles of the Cu-Sn alloy layer was not confirmed by SEM, and it was confirmed that a concave portion was formed (Sn remained) on the surface of the mutually bonded Cu-Sn alloy layer. In addition, the area occupied by the Sn layer in the outermost surface (the area ratio of Sn) is 15%, and the maximum depth of the concave portion (the maximum thickness of the Sn layer) is 0.20μm.

[0097] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.15 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0098] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.15 μm, and the maximum height Ry is 1.10 μm. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.23 and 0.23, respectively. In addition, the contact resistance value is 1.3 mΩ, and the contact resistance value after high temperature placement is 32 mΩ. In addition, the maximum value of the resistance value in the sliding test is a high value of 53 mΩ.

[0099] Comparative Example 4

[0100] The Sn-plated material was prepared by the same method as in Example 1 except that the surface of the substrate was processed with a ceramic rolling roller whose surface was not polished, the arithmetic mean roughness Ra was 0.20 μm, the maximum height Ry was 2.30 μm, the ten-point average roughness Rz was 1.58 μm, the thickness of the Cu plating layer was 0.3 μm, the thickness of the Sn plating layer was 0.7 μm, and the holding time of the heat treatment was 120 seconds. In this comparative example, the holding time after the Sn melted was 60 seconds in the 120 seconds of the heat treatment holding time, and the calculated result of the thickness of the Sn consumed after the Sn melted was 0.31 μm.

[0101] The Sn-plated material thus prepared was subjected to a coating layer analysis in the same manner as in Example 1, and the arithmetic mean roughness Ra and maximum height Ry of the surface, the average value of the angle θ, and the dynamic friction coefficient were calculated, and the contact resistance value was obtained, and the maximum value of the resistance value in the sliding test was obtained. In addition, in the plated substrate subjected to Sn plating, the ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer was 2.3, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the Ni plating layer was 1.75.

[0102] As a result, it was confirmed that the outermost layer was composed of Sn and Cu 6 Sn 5(Cu-Sn alloy), a concave portion is formed on the surface of the Cu-Sn alloy layer formed by the crystal grains of the Cu-Sn alloy (between the adjacent crystal grains of the Cu-Sn alloy), a Sn layer composed of Sn is formed in the concave portion, and a Cu-Sn alloy layer and a Sn layer exist on the outermost surface. In addition, the thickness of the Sn layer is 0.07 μm, and the thickness of the Cu-Sn alloy layer is 0.55 μm. In addition, it was confirmed by SEM that a concave portion was formed on the surface of the Cu-Sn alloy layer (with Sn remaining), and the calculated result of the average particle size of the crystal grains of the Cu-Sn alloy on the outermost surface was 1.6 μm. In addition, the calculated result of the ratio (D / T) of the average particle size (D) of the crystal grains of the Cu-Sn alloy in the outermost layer to the maximum thickness (T) of the Sn layer was 6.40. In addition, the area occupied by the Sn layer in the outermost surface (area ratio of Sn) was 10%, and the maximum depth of the concave portion (maximum thickness of the Sn layer) was 0.25 μm.

[0103] In addition, the base layer formed on the surface of the substrate of the Sn-plated material is composed of at least one of Ni and Cu-Ni alloy, and the thickness of the base layer is 0.10 μm. In addition, there is no Cu layer as an intermediate layer between the outermost layer of the Sn-plated material and the base layer, and the outermost layer is formed on the surface of the base layer.

[0104] In addition, the arithmetic mean roughness Ra of the surface of the Sn-plated material is 0.22 μm, the maximum height Ry is 1.78 μm, and the average value of the angle θ is 35.5°. In addition, the dynamic friction coefficients at loads of 0.7 N and 5 N are 0.36 and 0.26, respectively. In addition, the contact resistance value is 2.5 mΩ, and the contact resistance value after high temperature placement is 40 mΩ. In addition, the maximum value of the resistance value in the sliding test is a high value of 120 mΩ.

[0105] Tables 1 to 5 show the production conditions and properties of the Sn-plated materials of these Examples and Comparative Examples.

[0106] [Table 1]

[0107] Table 1

[0108]

[0109] [Table 2]

[0110] Table 2

[0111]

[0112] [Table 3]

[0113] Table 3

[0114]

[0115] [Table 4]

[0116] Table 4

[0117]

[0118] [Table 5]

[0119] Table 5

[0120]

Claims

1. A Sn-plated material, wherein Sn-plating is performed on the surface of a substrate composed of copper or a copper alloy, wherein: The surface of the substrate forms a base layer composed of at least one of Ni and Cu-Ni, and the surface of the base layer forms an outermost layer composed of a Cu-Sn alloy layer composed of a large number of Cu-Sn alloy grains, and a Sn layer located in a recess between adjacent Cu-Sn alloy grains on the outermost surface. The arithmetic mean roughness Ra of the outermost surface is 0.05 to 0.2 μm, the maximum height Ry is 0.3 to 1.5 μm, the area ratio of the Sn layer in the outermost surface is 20 to 57%, the ratio D / T of the average grain size D of the Cu-Sn alloy grains in the outermost layer to the maximum thickness T of the Sn layer is 2 to 7, and the maximum thickness of the Sn layer is smaller than the average grain size of the Cu-Sn alloy grains.

2. The Sn-plated material according to claim 1, characterized in that The Cu-Sn alloy layer is composed of Cu-Sn alloy and Cu-Ni-Sn alloy.

3. The Sn-plated material according to claim 2, characterized in that The Cu—Sn alloy is composed of Cu6Sn5, and the Cu—Ni—Sn alloy is composed of (Cu, Ni)6Sn5.

4. The Sn-plated material according to claim 1, characterized in that The average grain size of the Cu-Sn alloy crystal grains is 1.5 to 3 μm.

5. The Sn-plated material according to claim 1, characterized in that The maximum thickness of the Sn layer is 0.2-1.0 μm.

6. The Sn-plated material according to claim 1, characterized in that The average thickness of the Sn layer is 0.05-0.4 μm.

7. The Sn-plated material according to claim 1, characterized in that The thickness of the Cu-Sn alloy layer is 0.4-1.5 μm.

8. The Sn-plated material according to claim 1, characterized in that The thickness of the base layer is 0.05-0.5 μm.

9. The Sn-plated material according to claim 1, characterized in that: The area ratio of the Sn layer in the outermost surface is 45% or less.

10. A method for producing a Sn-plated material, characterized in that: The surface of a substrate composed of copper or a copper alloy is treated so that the arithmetic mean roughness Ra of the substrate surface is 0.05 to 0.2 μm, the maximum height Ry is 0.4 to 1.5 μm, and the ten-point average roughness Rz is 0.15 to 1.0 μm. Then, a Ni plating layer, a Cu plating layer and a Sn plating layer are formed on the surface of the substrate in sequence. Thereafter, a heat treatment is performed by setting the temperature and time in the range of 400 to 800°C and the holding time in the range of 40 to 1800 seconds to form an outermost layer composed of a Cu-Sn alloy layer composed of a large number of Cu-Sn alloy grains and a Sn layer located in a recess between adjacent Cu-Sn alloy grains on the outermost surface, so that the area ratio occupied by the Sn layer in the outermost surface is 20 to 57%, and at the same time, the maximum thickness of the Sn layer is smaller than the average grain size of the Cu-Sn alloy grains.

11. The method for producing a Sn-plated material according to claim 10, wherein: The thickness of the Ni plating layer is 0.05 to 0.5 μm, the thickness of the Cu plating layer is 0.1 to 0.7 μm, and the thickness of the Sn plating layer is 0.5 to 1.5 μm.

12. The method for producing a Sn-plated material according to claim 10, wherein: The ratio of the thickness of the Sn plating layer to the thickness of the Cu plating layer is 1.5 to 5, and the ratio of the thickness of the Sn plating layer to the sum of the thickness of the Cu plating layer and the thickness of the Ni plating layer is 1 to 3.

5.

13. The method for producing a Sn-plated material according to claim 10, wherein: The heat treatment is performed at set temperature and time so that the average grain size of the Cu-Sn alloy is 1.5 to 3 μm and the maximum thickness of the Sn layer is 0.2 to 1.0 μm within the range of 400 to 800° C. and 40 to 1800 seconds.

14. The method for producing a Sn-plated material according to claim 10, wherein: The heat treatment is performed by setting temperature and time so that the average thickness of the Sn layer is 0.05 to 0.4 μm within the range of a temperature of 400 to 800° C. and a holding time of 40 to 1800 seconds.

15. The method for producing a Sn-plated material according to claim 14, wherein: The temperature and time of the heat treatment are set so that the thickness (μm) of the Sn plating layer further consumed after the Sn plating layer is melted by the heat treatment is greater than {the thickness of the Sn plating layer before the heat treatment (μm) - 0.7 (μm)} and less than {the thickness of the Sn plating layer before the heat treatment (μm) - 0.35 (μm)}.

16. The method for producing a Sn-plated material according to claim 10, wherein: The area ratio of the Sn layer in the outermost surface is 45% or less.

17. An electrical component, characterized in that The Sn-plated material according to claim 1 is used as the material.